Industrial Policy for the Sustainable Development Goals Increasing the Private Sector_s Contribution. - OECD.; ProQuest (firma) (Paris : OECD Publishing, 2021)
How can governments support the private sector_s contribution to the Sustainable Development Goals (SDGs)? This book investigates the contribution of firms to the SDGs, particularly through their core business, taking into account inter-sectoral linkages and global value chains, using novel techniques and data sources.
References.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2022. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books